MICROTREMOR CHARACTERISTICS ON THE SURFACE OF BRIBIN UNDERGROUND RIVER, GUNUNG SEWU KARST AREA, BASED ON SPECTRAL ANALYSIS, ANALYSIS OF HORIZONTAL TO VERTICAL SPECTRAL RATIO (HVSR) CURVE, AND TIME FREQUENCY ANALYSIS (TFA) - NURHANAFI KHOLIS; wibowo Nugroho Budi; Sumardi Yosaphat (Jurnal Ilmu Fisika dan Terapannya (JIFTA), 2016)
This research aimed to determine microtremor characteristics in the area pass by Bribin Underground River and around its surface.Microtremor measured on fiveteen points on Bribin Underground Research line using Digital Portable Seismograph tools. The result of measurement recorded by three waves component and analized by Fast Fourier Transform (FFT) algoritm, and Konno-Ohmachi smoothing. Then, data were analized with Horizontal to Vertical Spectral Ratio (HVSR) and Time Frequency Analysis (TFA).The results of this research were microtremor characteristics on the surface of Bribin Underground River was determined by frequency at Fourier spectral peak of microtremor signal, these values were 0,44-0,78 Hz for EW horizontal component, 0,29-0,78 Hz for NS horizontal component, and 0,43-0,78 Hz for vertical component. Frequency of HVSR curve peak was between 1,0-15,5 Hz. Based on microtremor TFA curve of vertical component, research area was classified into two zones, and there was no spesific value which show (berkembangnya) Bribin Underground River line at research area based on frequency characteristics of Fourier spectral peak each microtremor component. The area (yang dilalui) Bribin Underground River was at 5,5-15,5 Hz based on HVSR curve analysis, and most was at zone II due to microtremor TFA curve characteristics of vertical component. Keywords: Microtremor Characteristics, Bribin Underground River